BEL1‐LIKE HOMEODOMAIN 11 regulates chloroplast development and chlorophyll synthesis in tomato fruit. (2nd June 2018) - Meng, Lanhuan; Fan, Zhongqi; Zhang, Qiang; Wang, Cuicui; Gao, Ying; Deng, Yikang; Zhu, Benzhong; Zhu, Hongliang; Chen, Jianye; Shan, Wei; Yin, Xueren; Zhong, Silin; et al.
Summary: Chloroplast development and chlorophyll(Chl)metabolism in unripe tomato contribute to the growth and quality of the fruit, however these mechanisms are poorly understood. In this study, we initially investigated seven homeobox‐containing transcription factors (TFs) with specific ripening‐associated expression patterns using virus‐induced gene silencing (VIGS) technology and found that inhibiting the expression of one of these TFs, BEL1‐LIKE HOMEODOMAIN11 (SlBEL11), significantly increased Chl levels in unripe tomato fruit. This enhanced Chl accumulation was further validated by generating stable RNA interference (RNAi) transgenic lines. RNA sequencing (RNA‐seq) of RNAi‐SlBEL11 fruit at the mature green (MG) stage showed that 48 genes involved in Chl biosynthesis, photosynthesis and chloroplast development were significantly upregulated compared with the wild type (WT) fruit. Genomic global scanning for Homeobox TF binding sites combined with RNA‐seq differential gene expression analysis showed that 22 of these 48 genes were potential target genes of SlBEL11 protein. These genes included Chl biosynthesis‐related genes encoding for protochlorophyllide reductase ( POR ), magnesium chelatase H subunit ( CHLH ) and chlorophyllide a oxygenase ( CAO ), and chloroplast development‐related genes encoding for chlorophyll a / b binding protein ( CAB ), homeobox protein knotted 2 ( TKN2 ) and ARABIDOPSIS PSEUDO RESPONSE REGULATOR 2‐LIKE ( APRR2 ‐like). Electrophoretic mobility shift assay (EMSA) and chromatin immunoprecipitation quantitative polymerase chain reaction (PCR) (ChIP‐qPCR) assays were employed to verify that SlBEL11 protein could bind to the promoters for TKN2, CAB and POR . Taken together, our findings demonstrated that SlBEL11 plays an important role in chloroplast development and Chl synthesis in tomato fruit. Significance Statement: The roles of a BEL1‐LIKE HOMEODOMAIN11 transcription factor ( SlBEL11) associated with specific ripening‐associated expression patterns in tomato fruit were investigated. Results demonstrate that SlBEL11 plays an important role in chloroplast development and Chl synthesis in tomato fruits.